Implementasi Model Fun Learning Terhadap Motivasi Belajar Siswa Mata Pelajaran Fiqih Di Kelas X MA Abu Amr Kab. Pasuruan - Munir, Miftakhul; Fatimah, Siti (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
The learning atmosphere in the classroom is felt by the students to be boring, makes them sleepy, and the learning motivation decreases, especially in fiqh subjects. Madrasah Aliyah Abu Amr, which is under the auspices of the Ar-Roudloh Berbaur Islamic boarding school, has more time in studying the Islamic religious education, thus making students prone to experience weariness and boredom which results in passive students when learning in class. Therefore, to increase learning motivation, as well as increase student learning activity in class X MA Abu Amr, it is carried out with a fun learning model in fiqh subjects. The purpose of this study was to determine the implementation and implications of the fun learning model on student motivation in fiqh subjects in class X MA Abu AmrPasuruan Regency. This research uses a qualitative descriptive approach with the type of case study research, namely research that is carried out intensively, in detail, and in depth on a particular incident or case to find out in depth how the implementation of the fun learning model on the learning motivation of class X MA Abu Amr. Data collection comes from interviews, observations, and documentation. Based on the results of the research on the implementation of the fun learning model on the learning motivation of class X MA Abu Amr students, there are the following: the fun learning model carried out by the teacher has a positive impact on students, changes in behavior and positive attitudes, activeness and full involvement of students in participating learning, as well as the growth and development of students' learning motivation, especially fiqh subjects which are marked by increased learning outcomes and student achievement in fiqh subjects, as well as increasing knowledge of fiqh knowledge more broadly than the material being taught.